The Role of Endothelium-Derived Relaxing Factor in The Regulation of SNP Induced Vasorelaxation: Sodium-Potassium-Chloride Cotransporter - Awla, Farhang A.; Mahmud, Almas M. R.; Shekha, Mudhir S. (Science Journal of University of Zakho, 2015)
Vascular endothelium plays a key role in the local regulation of vascular tone and vascular architecture. However, it is unclear whether the combination of NKCC cotransporter with endothelial mediated factor and potassium channel in rat aortic ring contributes in regulation of the vascular activity. In the current study, the potential role of endothelium-mediated relaxing factors and potassium channel in SNP induced vasorelaxation in precontracted isolated rat aortic rings in the presence of Bumetanide as NKCC blocker were investigated. The maximum vasorelaxation induced by SNP significantly blocked by the presence BUM. SNP induced relaxation was affected by combination of BUM with Indomethacin, Clotrimazole. TEA and BaCl2 significantly blocked of SNP induced relaxation in aorta preincubated with all blockers used, but BaCl2 showed a more potent effect as compared with others. These results indicate that SNP – induced vasorelaxation was mediated via EETs, Prostaglandin, BKCa and KIR pathways which ultimately enhanced the contribution of chloride transporter in aortic smooth muscle cells hyperpolarization and subsequent relaxation.